Targeted inhibition of tumor proliferation, survival, and metastasis by pentacyclic triterpenoids: Potential role in prevention and therapy of cancer - Shanmugam, M.; Nguyen, A.; Kumar, Alan Prem; Tan, B.; Sethi, G. (Elsevier, 2012)
Over the last two decades, extensive research on plant-based medicinal compounds has revealed exciting and important pharmacological properties and activities of triterpenoids. Fruits, vegetables, cereals, pulses, herbs and medicinal plants are all considered to be biological sources of these triterpenoids, which have attracted great attention especially for their potent anti-inflammatory and anti-cancer activities. Published reports in the past have described the molecular mechanism(s) underlying the various biological activities of triterpenoids which range from inhibition of acute and chronic inflammation, inhibition of tumor cell proliferation, induction of apoptosis, suppression of angiogenesis and metastasis. However systematic analysis of various pharmacological properties of these important classes of compounds has not been done. In this review, we describe in detail the pre-clinical chemopreventive and therapeutic properties of selected triterpenoids that inhibit multiple intracellular signaling molecules and transcription factors involved in the initiation, progression and promotion of various cancers. Molecular targets modulated by these triterpenoids comprise, cytokines, chemokines, reactive oxygen intermediates, oncogenes, inflammatory enzymes such as COX-2, 5-LOX and MMPs, anti-apoptotic proteins, transcription factors such as NF-κB, STAT3, AP-1, CREB, and Nrf2 (nuclear factor erythroid 2-related factor) that regulate tumor cell proliferation, transformation, survival, invasion, angiogenesis, metastasis, chemoresistance and radioresistance. Finally, this review also analyzes the potential role of novel synthetic triterpenoids identified recently which mimic natural triterpenoids in physical and chemical properties and are moving rapidly from bench to bedside research.